Defining the pknH Transcriptional Network in the Animal Tuberculosis bacillus, Mycobacterium bovis. Issue 5 (27th May 2022) - Kerins, Anne; Farrell, Damien; Gordon, Stephen V.
Abstract : The Mycobacterium tuberculosiscomplex (MTBC) is a group of bacteria that show more than 99% genetic identity, yet they diverge in their host preference and the severity of associated disease. Mycobacterium bovis causes the disease in cattle and poses an economic challenge, with the cost of Irelands TB Eradication Scheme predicted to exceed €90 million in 2020. The aim was to focus on the RD900 and pknH gene network in MTBC members. ThepknH gene encodes a transmembrane serine threonine protein kinase, that plays a role in the regulation of signalling pathways in the mycobacterial cell and has been linked to virulence. The RD900 or "region of difference 900" contains the tbD2 and pknH2 genes. The part of the genome that contains this region varies substantially across MTBC members. The results of RNA-seq analysis showed that there are statistically significant levels of differential gene expression in wildtype and knock-in M. bovis strains. The RD900 analysis across the MTBC showed that there is variation in this important genomic region. Analysis carried out by Mata et al. 2020, showed that this RD900 region had been independently lost in different MTBC lineages and strains. M. bovis has retained the RD900 region and this is believed to be linked to its increased virulence. The majority of the M . africanum strains were found to possess the standard pknH, tbD2, pknH2, embR gene arrangement as is found in M. africanum GM041182, the strain that is typically used as a reference. Based on work of Mata et al., 2020.